HADIS TENTANG ILMU PERSPEKTIF SYI’AH DAN SUNNI: TELAAH KITAB AL-KAFI AL-KULAINI DAN SHAHIH BUKHARI (Thobaqot: Jurnal Ilmu Hadis, 2024)
This study compares hadith on science from the Sunni and Shi'a perspectives, using two major books: al-Kafi by al-Kulaini and Sahih Bukhari. Sunnis and Shi'a use the hadith books as their primary guide in addition to the Qur'ān, but differences in the assessment of hadith quality often hamper communication. The Shi'a consider a hadith to be authentic if its chain of transmission extends back to the infallible imam, with fair narrators from the Imamiyah group. Sunnis consider a hadith to be authentic if its chain of transmission extends directly to the Prophet, with fair and accurate narrators who are free from error. This study utilized the descriptive method of analysis with a qualitative approach. The results show fundamental differences in the assessment of hadith quality between the two traditions, which affect their concepts of knowledge. Al-Kafi emphasizes the continuity of the sanad up to the ma'shum imam and the fairness and reliability of the narrators, while Sahih Bukhari emphasizes the continuity of the sanad up to the Prophet and the fairness and accuracy of the narrators. It is hoped that this study will provide a better understanding of the views of science in the Sunni and Shi'a traditions and the role of the hadith books in the development of Islamic science.